Self‐Regulation and Power: How Self‐Regulatory Failures Can Enhance Social Power. Issue 1 (January 2016) - McIntyre, Jason C.; von Hippel, William; Barlow, Fiona Kate
Abstract: Low self‐control is often associated with poor life outcomes. Here, we propose that self‐control failures may also provide social benefits by signaling and maintaining power. We identify several pathways by which reduced self‐control can assist in ascending social hierarchies. First, the self‐enhancing tendencies adopted by people with low self‐control may contribute to making positive first impressions and advertising power to new acquaintances. The direct and disinhibited communication styles that stem from self‐control failures may also enhance power and lubricate difficult social interactions. Disinhibited aggression can help people maintain and acquire material resources and establish dominance over rivals. Finally, the parallels between the behavior of people with low self‐control and people with power (e.g., self‐enhancement, disinhibition, approach‐orientation, aggression) suggest that people with impaired self‐control will be perceived as more powerful than people with intact self‐control. Evidence for these propositions and directions for future research are discussed.